Correction to: Updates in Genetic Testing Guidelines for Breast Cancer Susceptibility Genes: a Change in the Paradigm - Lorena Gonzalez; Laura Kruper (Current Breast Cancer Reports, 2021)
A Correction to this paper has been published: 10.1007/s12609-021-00425-z